Climatologia da temperatura do ar e temperatura do ponto de orvalho em Belém-Pará - MONTEIRO, Luciana Danielle Antunes (2019)
Were analyzed hourly data, monthly and annual air temperature and dew point temperature of the station meteorological located at the international airport of Belem (EMABE-SBBE) the period of 29 years. In order to perform the climatology of air temperature and dew point temperature for the city of Belem-Para in the period from 1975 to 1994 and from 2003 to 2011. Verify the occurrence of extreme events such temperatures for daytime and nighttime. It was evidenced by the distribution of frequency, the city of Belem has a higher frequency of air temperature in the range of 24, 4 °C to 25, 2 °C. In the period 2003 to 2011 this range represents 21% of the total data and 17% in the period 1975 to 1994. There is also an increase in the frequency range 34,0 °C to 34,8 °C in the period 2003 to 2011. The dew point temperature obtained more frequency in the range 23, 4 °C to 24, 0 °C over the period 1975 to 1994. However at temperatures from 2003 to 2011 had higher frequency in the range 24, 0 °C to 24, 6 °C. The annual air temperature presents maximum values in the less rainy season (June to November), with an average speed of 31, 2 °C at 13:00 (HL) in November. The lowest average temperatures are recorded in the months of February, March and April, corresponding to the months of greater cloudiness and precipitation, which contributes to low heat. Through the method of percentiles, it is observed that in the period 2003 a 2011 there was an increase in the percentage of extreme events maximum air temperature compared to the period 1975 to 1994, contrast the year 2007 with 27% of air temperatures maximum extremes.